2004
DOI: 10.1080/02841860310020339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life/life satisfaction in women with breast cancer in complementary and conventional care

Abstract: The aim was to study the perceived quality of life/life satisfaction in a sample of women with breast cancer who were treated in a hospital with alternative/complementary care and the same variables in individually matched patients who received only conventional medical treatment. A non-randomized controlled trial design with repeated measurements was used. Sixty women with breast cancer treated with anthroposophic medicine (ABCW) and 60 with conventional medicine (CBCW) were included and 36 matched pairs took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 13 publications
(13 reference statements)
3
53
0
1
Order By: Relevance
“…Previous studies have evaluated AM therapy including RMT in inpatient settings and found improved quality of life in breast cancer patients; 5 improved coping with chronic musculoskeletal pain; 6 high anorexia nervosa cure rates; 3 and reduced pain, reduced medication use, and earlier return to work in lumbar disc disease. 3 In accordance with these findings, our primary care study of patients with predominantly musculoskeletal and mental diseases demonstrated longstanding clinically relevant improvements in disease symptoms and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated AM therapy including RMT in inpatient settings and found improved quality of life in breast cancer patients; 5 improved coping with chronic musculoskeletal pain; 6 high anorexia nervosa cure rates; 3 and reduced pain, reduced medication use, and earlier return to work in lumbar disc disease. 3 In accordance with these findings, our primary care study of patients with predominantly musculoskeletal and mental diseases demonstrated longstanding clinically relevant improvements in disease symptoms and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies in inpatient settings suggest that RMT can have clinically relevant effects. 3,5,6 However, these studies evaluated several AM therapies, and only a proportion of the patients received RMT. Here we present a long-term study of RMT users.…”
Section: Postulatedmentioning
confidence: 99%
“…In a prospective clinical trial, however, a breast cancer group using CAM reported better QOL at 1-year follow-up than non-CAM users. 15 CAM user cancer survivors also reported less deterioration of perceived health from pre-topost-cancer diagnosis than non-CAM users 16 and better QOL.…”
Section: Introductionmentioning
confidence: 92%
“…Patients with breast cancer treated with both CAM and conventional treatment reported better QOL than patients treated only with conventional treatment at 1-year follow-up. 15 CAMusing patients reported less deterioration of perceived health from pre-to postcancer diagnosis. 16 Women who consulted an alternative service in the prior year tended to have reduced stress and depression over time.…”
Section: Cam Associations With Psychosocial and Behavioral Factorsmentioning
confidence: 99%
“…The following findings from clinical studies summarize the therapeutic effects that have been observed with mistletoe [27][28][29][30][31][32][33][34][35][36][37][38][39] :…”
Section: Mainstream Medicine and Mistletoementioning
confidence: 99%